Recopilación de fuentes para la historia Mapuche, siglos XVII, XVIII y XIX Edición y comentarios - Rinke, Stefan; Chacón, Nelson (Historamericana, 2021)
This collection of sources sheds light on the history of the Mapuche between the 16th and 19th centuries. The source material comes from various institutions such as the Archivo Franciscano de Chile, Chillán (Fondo de Asuntos Varios) and the Archivo Nacional de Chile.